2022
DOI: 10.3390/jcdd9050136
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms and Clinical Implications of Endothelial Dysfunction in Arterial Hypertension

Abstract: The endothelium is composed of a monolayer of endothelial cells, lining the interior surface of blood and lymphatic vessels. Endothelial cells display important homeostatic functions, since they are able to respond to humoral and hemodynamic stimuli. Thus, endothelial dysfunction has been proposed as a key and early pathogenic mechanism in many clinical conditions. Given the relevant repercussions on cardiovascular risk, the complex interplay between endothelial dysfunction and systemic arterial hypertension h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
29
0
7

Year Published

2022
2022
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(37 citation statements)
references
References 164 publications
(202 reference statements)
1
29
0
7
Order By: Relevance
“…Endothelial dysfunction is not a specific feature of hypertension, but it is common to the majority of cardiovascular risk factors [ 1 ]. In particular, patients with hypertension presented greater apoptosis in the endothelium [ 34 , 40 ]. In line with recent reports, cell apoptosis investigated by Annexin V–FITC/PI flow cytometry assay and Hoechst 33342/PI double staining revealed that the percentage of apoptotic cells induced by Ang II was notably reduced by acacetin.…”
Section: Discussionmentioning
confidence: 99%
“…Endothelial dysfunction is not a specific feature of hypertension, but it is common to the majority of cardiovascular risk factors [ 1 ]. In particular, patients with hypertension presented greater apoptosis in the endothelium [ 34 , 40 ]. In line with recent reports, cell apoptosis investigated by Annexin V–FITC/PI flow cytometry assay and Hoechst 33342/PI double staining revealed that the percentage of apoptotic cells induced by Ang II was notably reduced by acacetin.…”
Section: Discussionmentioning
confidence: 99%
“…2). In addition, ECs are also involved in smooth muscle cells proliferation and migration via balanced vasoconstriction and vasodilation as well as platelets aggregation and adhesion 2,32 and thrombogenesis. Thus, unsettling this tightly regulated equilibrium leads to endothelial dysfunction.…”
Section: Endothelial Vascular Tone and Vascular Homeostasismentioning
confidence: 99%
“…It has been reported that about 87% of transient ischemic attacks/minor strokes (TIAs/MSs) are caused by narrowed or obstructed blood vessels in the brain cutting off the blood flow to neurons ( Ganzer et al, 2016 ; Yu and Coutts 2018 ; Panuganti et al, 2022 ). Several studies demonstrate that the pathogenesis of hypertension is associated with oxidative stress, with a reduction in the bioavailability of nitric oxide (NO) accompanied by endothelial dysfunction and alterations in the structure of cerebral blood vessels, disrupting complex vasoregulatory mechanisms ( Atochin and Huang 2011 ; Zhu et al, 2016 ; Quick et al, 2021 ; Ambrosino et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%